Implikasi Pengaturan Alat Kontrasepsi dalam KUHP Baru Terhadap Kebijakan Kesehatan Reproduksi - Siti Nurhaliza Nuwa (Jurnal Hukum Caraka Justitia, 2025)
The regulation of contraceptives in Indonesia's new Criminal Code (KUHP) has sparked widespread debate regarding its impact on national reproductive health policies. The background to this study is based on concerns that a number of articles in the new KUHP, particularly those restricting the distribution and education of contraceptives, have the potential to hinder public access to comprehensive reproductive health services. This study aims to critically analyze the implications of these regulations on the effectiveness of family planning programs, the protection of reproductive rights, and the achievement of public health goals in Indonesia. The research method used is normative legal research with a legislative and policy analysis approach, supported by a literature review and relevant document analysis. The findings of this study indicate that restrictions on the distribution of contraceptives in the new Criminal Code may create legal uncertainty for health workers and family planning program implementers, and potentially increase the rate of unwanted pregnancies and reproductive health risks, particularly among adolescents and women. Additionally, these regulations are deemed inconsistent with Indonesia's commitment to protecting human rights in the field of reproductive health and may hinder the achievement of national health development targets.